DEVELOPING LEARNING MEDIA BASED ON AUGMENTED REALITY (AR) TO IMPROVE LEARNING MOTIVATION - Ridho Dedy Arief Budiman (JETL (Journal of Education, Teaching and Learning), 2016)
This research aims to reveal the development of Augmented Reality-based learning media to increase motivation to learn computer assembly materials. This research is an research and development type. The population was ninth students of SMP Harapan Ananda Kubu Raya totaling 112 students. The sample was 68 students with proportional random sampling technique. Data Collection using a questionnaire. To test the hypothesis, one-tailed t-test was used. Data analysis was performed descriptively. The results showed that one-tailed t-test data is posttest questionnaire motivation experimental class and control sig 0.000 <α 0.05, so it can be concluded that the motivation to learn the experimental group was higher than the control group.